Effect of Alirocumab on Coronary Calcification in Patients With Coronary Artery Disease - Gao, Fei; Li, Yue Ping; Ma, Xiao Teng; Wang, Zhi Jian; Shi, Dong Mei; Zhou, Yu Jie (Frontiers in Cardiovascular Medicine, 2022)
Background: Proprotein convertase subtilisin kexin type 9 (PCSK9) inhibitors have been documented with significantly reduction in LDL cholesterol levels and cardiovascular events. However, evidence regarding the impact of PCSK9 inhibitors on coronary calcification is limited. Methods: Eligible patients with intermediate coronary lesions and elevated LDL cholesterol values were randomized to either alirocumab 75 mg Q2W plus statin (atorvastatin 20 mg/day or rosuvastatin 10 mg/day) therapy or standard statin therapy. Calcium score based on coronary computed tomographic angiography at baseline and follow up were compared. Results: Compared with baseline levels, LDL cholesterol were significantly decreased in both groups, while the absolute reduction of LDL cholesterol levels were higher in patients treated with alirocumab (1.69±0.52 vs. 0.92±0.60, P<0.0001). Additionally, patients in alirocumab group demonstrated a significant reduction of Lp(a) levels, whereas it was not observed in the standard statin group. Notably, greater increases in the percentage changes of CAC score (10.6% [6.3–23.3] vs. 2.9% [-6.7–8.3]; P<0.0001) were observed in the statin group compared to the alirocumab group. Consistently, CAC progression was significantly lower in the alirocumab group than in the standard statin group (0.6%±2.2% vs. 2.7%±2.3%; P=0.002). Conclusions: Study indicated that administration of the PCSK9 inhibitors to statins produced significantly lower rate of CAC progression in patients with coronary artery disease. Further studies with CAC progression and their clinical outcomes are needed.